Making gas‐CCS a commercial reality: The challenges of scaling up. Issue 5 (10th July 2017) - Diego, Maria Elena; Akram, Muhammad; Bellas, Jean‐Michel; Finney, Karen N.; Pourkashanian, Mohamed
Abstract: Significant reductions in CO2 emissions are required to limit the global temperature rise to 2°C. Carbon capture and storage (CCS) is a key enabling technology that can be applied to power generation and industrial processes to lower their carbon intensity. There are, however, several challenges that such a method of decarbonization poses when used in the context of natural gas (gas‐CCS), especially for solvent‐based (predominantly amines) post‐combustion capture. These are related to: (i) the low CO2 partial pressure of the exhaust gases from gas‐fired power plants (∼3‐4%vol. CO2 ), which substantially limits the driving force for the capture process; (ii) their high O2 concentration (∼12‐13%vol. O2 ), which can degrade the capture media via oxidative solvent degradation; and (iii) their high volumetric flow rates, which means large capture plants are needed. Such post‐combustion gas‐CCS features unavoidably lead to increased CO2 capture costs. This perspective aims to summarize the key technologies used to overcome these as a priority, including supplementary firing, humidified systems, exhaust gas recirculation and selective exhaust gas recirculation. These focus on the maximum CO2 levels achievable for each, as well as the electrical efficiencies attainable when the capture penalty is taken into account. Oxy‐turbine cycles are also discussed as an alternative to post‐combustion gas‐CCS, indicating the main advantages and limitations of these systems together with the expected electrical efficiencies. Furthermore, we consider the challenges for scaling‐up and deployment of these technologies at a commercial level to enable gas‐CCS to play a crucial role in a low‐carbon future. © 2017 The Authors. Greenhouse Gases: Science and Technology published by Society of Chemical Industry and John Wiley & Sons, Ltd.